2020
DOI: 10.15244/pjoes/115273
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals Pollution Characteristics and Health Risk Assessment of Farmland Soils and Agricultural Products in a Mining Area of Henan Province, China

Abstract: The development of mineral resources has promoted the rapid development of the social economy. However, mining and mineral processing are regarded as a primary source of heavy metals contamination in the environment due to activities of mineral excavation, ore transportation, smelting, and refining [1][2][3][4][5]. Among all mining wastes, tailings are a solid waste with especially high toxic heavy metals produced in the process of mining, mineral processing and smelting, which are considered the greatest thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…As shown in Figure 3 , the results indicated that the Pb, Cr, Cu, and Cd contents in the tailings were significantly higher than the corresponding background values associated with the soil in Henan Province [ 60 ]. Particularly, Pb was the element with the highest concentration of 1377 mg kg −1 , which was approximately 61.75 times the allowable value.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 3 , the results indicated that the Pb, Cr, Cu, and Cd contents in the tailings were significantly higher than the corresponding background values associated with the soil in Henan Province [ 60 ]. Particularly, Pb was the element with the highest concentration of 1377 mg kg −1 , which was approximately 61.75 times the allowable value.…”
Section: Resultsmentioning
confidence: 99%
“…Soils were sampled in 2014 and 2017 to evaluate changes of Cd, Cu, Mn, Pb, and Zn concentrations. The research evaluates sources of soil pollution in the study area to determine processes creating these patterns in soil chemistry; similar studies can be found in other works [27][28][29][30][31]. Finally, interpolation was done to estimate pollution levels across the entire study area, related to the works of Hou et al and Luzio et al [32,33].…”
Section: Introductionmentioning
confidence: 89%
“…The ratio between the total metal content in the soil sample (Cm) and world average shale values, as a background values, were used for the Cf calculation: Cf = C metal /C shale . See the grading standards for the ER and RI in the Table 2 [28,29].…”
Section: Statistical Analysesmentioning
confidence: 99%
“…They have become health hazards worldwide due to their non-biodegradability and bioaccumulation. Biological activities include rock weathering and volcanic eruptions, while anthropogenic activities include mining, ores smelting, and phosphate fertilizer ( 6 ).…”
Section: Introductionmentioning
confidence: 99%